Eksistensialisme sebagai Landasan Metafisika Worldview Islam: Analisis Gagasan Al-Attas tentang Wujud - Rakhmat, Aulia (Tasfiyah: Jurnal Pemikiran Islam, 2022)
This study aims to examine the idea of al-Attas’ existentialism which is embodied in his conception of wujud and its relationship with worldview. Al-Attas’ definition of worldview, the Islamic vision of WujÅ«d, indicates the significance of wujÅ«d in the worldview building formulated by al-Attas. However, al-Attas’s conception of wujÅ«d is overlooked in academic studies, even though this concept is a crucial theme in his philosophical thinking. This study applies descriptive and analytical methods as well as a philosophical approach to analyze al-Attas’ works. This paper argues that al-Attas’s idea of worldview is built on the principle of existentialism which is inspired by the concept of Waá¸¥dah al-WujÅ«d Sufism. It states that wujÅ«d is the true reality, while what is called quiddity or essence is just a mode of wujÅ«d. Thus, the structure of reality is WujÅ«d in its Unity and Diversity which is nothing but a manifestation of al-á¸¤aqq.